2016
DOI: 10.1128/jb.00507-16
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Undecaprenyl Pyrophosphate Phosphatases Disrupts Cell Envelope Biogenesis in Bacillus subtilis

Abstract: The integrity of the bacterial cell envelope is essential to sustain life by countering the high turgor pressure of the cell and providing a barrier against chemical insults. In Bacillus subtilis, synthesis of both peptidoglycan and wall teichoic acids requires a common C 55 lipid carrier, undecaprenyl-pyrophosphate (UPP), to ferry precursors across the cytoplasmic membrane. The synthesis and recycling of UPP requires a phosphatase to generate the monophosphate form Und-P, which is the substrate for peptidogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 56 publications
9
58
0
Order By: Relevance
“…Indeed, by sequencing the two key elements of the CRISPRi system, the sgRNA and dcas9 , we found that most of the suppressor strains contain loss‐of‐function mutation in the dcas9 coding sequence (Fig EV4B). This is similar to observations made for the CRISPRi system in Bacillus subtilis (Zhao et al , ).…”
Section: Resultssupporting
confidence: 91%
“…Indeed, by sequencing the two key elements of the CRISPRi system, the sgRNA and dcas9 , we found that most of the suppressor strains contain loss‐of‐function mutation in the dcas9 coding sequence (Fig EV4B). This is similar to observations made for the CRISPRi system in Bacillus subtilis (Zhao et al , ).…”
Section: Resultssupporting
confidence: 91%
“…Cells lacking r M are significantly more sensitive to drugs that interrupt essential steps in the construction of PG, which is at least partially due to an inability to induce genes involved in PG homeostasis (Mascher et al, 2007;Luo and Helmann, 2012). Although the roles of many genes in the r M regulon have been well defined (Cao et al, 2005;Eiamphungporn and Helmann, 2008;Meeske et al, 2015;Meeske et al, 2016;Zhao et al, 2016), the contributions of each r M target operon to antibiotic resistance are incompletely understood. Here, we show that antibiotic-dependent induction of the Spx regulon protects cells against killing by cell wall antibiotics (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LFH PCR, chromosomal and plasmid DNA transformation was performed as previously stated (Zhao et al, ). The kanamycin resistance and MLS resistance cassettes were PCR amplified from plasmids pDG780 and pDG646 respectively (Guerout‐Fleury et al, ).…”
Section: Methodsmentioning
confidence: 99%